RISK FACTORS FOR THE FORMATION OF BORN HEART DEFECTS IN CHILDREN IN THE FERGHANA REGION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The authors conducted a study on the influence of risk factors on the frequency and structure of congenital heart defects in children in the Ferghana region. It has been established that the incidence of VP is 2.6 cases per 1,000 births, which is 4 times more common in children living in rural areas. Analysis by cities and districts.